2012
DOI: 10.1103/physreve.86.051604
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing instabilities and delamination in elastic bilayers: A linear stability analysis

Abstract: A linear stability analysis is presented to understand the instabilities that arise in an elastic bilayer, consisting of a very thin bottom layer (thickness < 100 nm) that acts as a wetting film and a top layer that acts as an adhesive film, when placed in contact proximity with an external rigid contactor. Depending on whichever layer is more compliant, "squeezing modes" of instability with a variety of length scales ranging from <<3h to <<3h (h: bilayer thickness) are found to be possible. The least length s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…More recently, Naumov and colleagues reported composite hygro­responsive actuators in which high directionality and complex modes of actuation were achieved by incorporating glass fibers as directing and reinforcing materials into agarose gels . However, a significant limitation of multilayered and composite systems lies at the layer–layer interface, the proverbial “weak link”, where delamination occurs with prolonged use. , Thus, materials and fabrication strategies that exploit single-layer materials that predictably deform in a predefined direction may be advantageous. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Naumov and colleagues reported composite hygro­responsive actuators in which high directionality and complex modes of actuation were achieved by incorporating glass fibers as directing and reinforcing materials into agarose gels . However, a significant limitation of multilayered and composite systems lies at the layer–layer interface, the proverbial “weak link”, where delamination occurs with prolonged use. , Thus, materials and fabrication strategies that exploit single-layer materials that predictably deform in a predefined direction may be advantageous. , …”
Section: Introductionmentioning
confidence: 99%
“…9 However, a significant limitation of multilayered and composite systems lies at the layer−layer interface, the proverbial "weak link", where delamination occurs with prolonged use. 23,24 Thus, materials and fabrication strategies that exploit single-layer materials that predictably deform in a predefined direction may be advantageous. 25,26 In this Article, we report all-protein materials that are humidity-and electro-active, fabricated from the engineered repeat protein Consensus Tetratricopeptide Repeat protein (CTPR18).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is unlike thin liquid films (h < 100 nm) where the instabilities developed were long waved (λ ∼ h 2 ) and highly influenced by surface tension as well as the nature of interactions present between the film and the substrate [62][63][64][65][66][67][68][69][70]. Much effort has since been directed to reduce the instability length scales further, primarily, by using elastic films cast in bilayer configuration [71][72][73][74][75][76][77][78][79]. This method, however, faces difficulty since casting the bilayers is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…This method, however, faces difficulty since casting the bilayers is problematic. Moreover, in the case of bilayers cast with films of very different elastic stiffness, there is a possibility of delamination at the film-film interface [79], which might not always be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature exists in the area of morphological patterning of soft elastic surfaces in adhesive contact or in peeling configuration in close proximity with an external contactor where patterns formed are of length scales 3 h or 4 h depending on the contactor-film configuration and are independent of the nature of interactions present between the film and the contactor and the elastic modulus of the film. In yet another work on hydrogel sandwiched between rigid plates, length scales 7 h have been observed, and it is proposed that these large length scales can affect the fracture modes as well as the adhesive strength of the hydrogel . There has been a lot of interest lately in forming miniaturized elastic film patterns of length scales less than ∼3 h by various methods like elastic bilayers and using topographically patterned substrates. Recent works on using a patterned substrate have suggested that patterned substrates yield reduced length scale patterns due to the lateral variation in film thickness which results in lateral variation in elastic film stiffnesses. , …”
Section: Introductionmentioning
confidence: 99%